Everyday utopia : what 2000 years of wild experiments can teach us about the good life - Ghodsee, Kristen Rogheh, 1970- (Simon & Schuster, 2023)
"A spirited tour through 2,500 years of utopian thinking and experiments to tease out better ways of imagining our domestic lives - from childrearing and housing to gender roles and private property - and a look at the communities putting these seemingly fanciful visions into practice today"--